MSRC at TREC 2011 Crowdsourcing Track - Bennett, Paul; Kamar, Ece; Kazai, Gabriella (In Proceedings of TREC 2011, 2011)
Crowdsourcing useful data, such as reliable relevance labels for pairs of topics and documents, requires a multidisciplinary approach that spans aspects such as user interface and interaction design, incentives, crowd engagement and management, and spam detection and filtering. Research has shown that the design of a crowdsourcing task can significantly impact the quality of the obtained data, where the geographic location of crowd workers was found to be a main indicator of quality. Following this, for the Assessment task of the TREC crowdsourcing track, we designed HITs to minimize attracting spam workers, and restricted participation to workers in the US. As an incentive, we included the possibility of a bonus pay of 5 for the best performing workers. When crowdsourcing relevance judgments, multiple judgments are typically obtained to provide greater certainty as to the true label. However, combining these judgments by a simple majority vote not only has the flawed underlying assumption that each assessor has comparable accuracy but also ignores the impact of topic specific effects (e.g. the amount of topic-expertise needed to accurately judge). We provide a simple probabilistic framework for predicting true relevance from crowdsourced judgments and explore variations that condition on worker and topic. In particular, we focus on the topic conditional model that was our primary submission for the Consensus task of the track.